Use of level specific ce-chirp auditory brainstem response with high rates and objective algorithm in infants population - Chahed, Norashikin; Dzulkarnain, Ahmad Aidil Arafat; Jamaluddin, Saiful Adli (2021)
Introduction: Universal Newborn Hearing Screening (UNHS) aims for early diagnosis, intervention, and follow-up of hearing-impaired babies. One of the tools used for the UNHS is the Auditory Brainstem Response (ABR). The LS CE Chirp is the recent innovated stimulus to elicit ABR and it is able to provide most neural synchrony in combination with high stimulus repetition rates and signal to noise ratio (SNR) objective algorithm, namely F-test at multiple points (Fmp). These techniques are potentially to reduce test time from the improvement in SNR of the ABRs recordings. This study aims to compare the ABR test time, amplitude, and absolute latencies of waves (I, III, and V), and threshold estimations among the ABRs obtained from the combinations of LS CE Chirp and Click stimuli at multiple intensity levels and stimulus repetition rates using both visual detection and objective SNR detection.